Insights into the effect of dilute acid, hot water or alkaline pretreatment on the cellulose accessible surface area and the overall porosity of Populus1. Issue 8 (3rd August 2015) - Meng, Xianzhi; Wells, Tyrone; Sun, Qining; Huang, Fang; Ragauskas, Arthur
<x xml:space="preserve">Abstract</x> Insights into the effect of dilute acid, hot water and alkaline pretreatment on the cellulose accessible surface area and the overall porosity of Populus.